Southern African Cumacea: Volume-1 - Day, Jennifer Ann (Department of Biological Sciences, 2023)
Several thousand cumacear.s have been examined from over six hundred benthic samples collected around the coast of southern Africa (south of 20°s). The taxonomy of the families Bodotriidae, Lampropidae, Ceratocumatidae, ·Gynodiastylidae and Diastylidae has been studied in detail and papers on the southern African representatives of the first three families have been published in the Annals of the South African Museum. In. the five families studied, seventy-five species are known in southern Afric~n waters and forty-five of these are here presented as new. There are four new genera (Alticuma, Austrocuma, Mossambicuma and Haliana). A group of six genera, Allodiastylis, Zimmeriana, Sheardia, Dicoides, Gynodiastylis and Haliana, is removed from the Diastylidae and returned to the previously rejected family Gynodiastylidae Stebbing, 1912. · A complf!te synonymy is given for each species, together with a list of / previous records and data on type material where this is available. All species examined by the author are described and figured. The abundance of Iphinoe stebbingi in False Bay. is positively correlated with depth~ particle size and organic content of the substrate, while the abundance of Diastylis algoae correlates only with depth. These results are discussed in ·relation to the biology of the two species.